Potential risks associated with traditional herbal medicine use in cancer care: A study of Middle Eastern oncology health care professionals. Issue 4 (24th November 2015) - Ben‐Arye, Eran; Samuels, Noah; Goldstein, Lee Hilary; Mutafoglu, Kamer; Omran, Suha; Schiff, Elad; Charalambous, Haris; Dweikat, Tahani; Ghrayeb, Ibtisam; Bar‐Sela, Gil; Turker, Ibrahim; Hassan, Azza; et al.
Abstract : BACKGROUND: The authors assessed the use of herbal medicine by Middle Eastern patients with cancer, as reported by their oncology health care professionals (HCPs). Herbal products identified by the study HCPs were evaluated for potential negative effects. METHODS: Oncology HCPs from 16 Middle Eastern countries received a 17‐item questionnaire asking them to list 5 herbal products in use by their patients with cancer. A literature search (PubMed, Micromedex, AltMedDex, and the Natural Medicine Comprehensive Database) was conducted to identify safety‐related concerns associated with the products listed. RESULTS: A total of 339 HCPs completed the study questionnaire (response rate of 80.3%), identifying 44 herbal and 3 nonherbal nutritional supplements. Safety‐related concerns were associated with 29 products, including herb‐drug interactions with altered pharmacodynamics (15 herbs), direct toxic effects (18 herbs), and increased in vitro response of cancer cells to chemotherapy (7 herbs). CONCLUSIONS: Herbal medicine use, which is prevalent in Middle Eastern countries, has several potentially negative effects that include direct toxic effects, negative interactions with anticancer drugs, and increased chemosensitivity of cancer cells, requiring a reduction in dosedensity. Oncology HCPs working in countries in which herbal medicine use is prevalent need to better understand the implications of this practice. The presence of integrative physicians with training in complementary and traditional medicine can help patients and their HCPs reach an informed decision regarding the safety and effective use of these products. Cancer 2016;122:598–610. © 2015 American Cancer Society . Abstract : The current study explores the perspectives of oncology healthcare providers from 16 countries across the Middle East concerning the use of complementary and traditional medicine in an attempt to identify potential safety‐related concerns associated with herbal practice. The authors report that 29 of the 44 identified herbal products were associated with safety‐related concerns that included herb‐drug interactions, toxic effects of the herbal components, and alterations in the response of cancer cells to chemotherapy.